Análisis de la evolución de la criptomoneda bitcoin en el mundo entre el 2010 y el 2018 (2018)
Cryptocurrencies have slowly managed to take their place in the panorama of global economic transfers, thanks to the advantages offered by traditional financial systems. By focusing on Bitcoin we can see that this cryptocurrency is global, without political, economic or social barriers. since it is based on a "person to person" system, allowing the exchange of value through the Internet without the need for a central institution or human interaction for its operation, it also has almost imperceptible transaction costs, depends on the internal movements of the platform of supply and demand, then seen in this way Bitcoin could change the current way of doing business in the world.